2003
DOI: 10.1080/0142159031000136716
|View full text |Cite
|
Sign up to set email alerts
|

Stress among medical students in a Thai medical school

Abstract: This study aimed to determine the prevalence and sources of stress among Thai medical students. The questionnaires,which consisted of the Thai Stress Test (TST) and questions asking about sources of stress, were sent to all medical students in the Faculty of Medicine, Ramathibodi Hospital, Thailand. A total of 686 students participated. The results showed that about 61.4% of students had some degree of stress. Seventeen students (2.4%) reported a high level of stress. The prevalence of stress is highest among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

37
257
13
26

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(333 citation statements)
references
References 2 publications
37
257
13
26
Order By: Relevance
“…It has been observed that medical students have marked undue stresses during pre and examination period 23 . The results are well in agreement with the previous studies were students experience stress during the first year but not in subsequent years 24,25,26 . The medical students are always vulnerable to stress due to their high competitive environment.…”
Section: Discussionsupporting
confidence: 93%
“…It has been observed that medical students have marked undue stresses during pre and examination period 23 . The results are well in agreement with the previous studies were students experience stress during the first year but not in subsequent years 24,25,26 . The medical students are always vulnerable to stress due to their high competitive environment.…”
Section: Discussionsupporting
confidence: 93%
“…According to the World Health Organization (WHO), a person could be termed depressed if he shows a variable combination of loss of interest or pleasure, feeling of guilt, feeling hopeless, feeling restless, low mood, low self-esteem, disturbed sleep, disturbed concentration or disturbed appetite [3]. A number of several studies have documented stress among medical students ranging from 12% to 73% [4][5][6][7] In 2015, Kulsoom and Afsar showed that the smoking and female sex were associated with higher levels of depression, anxiety or stress compared to other medical students amongst college of medicine at Al-Faisal University, Riyadh, Saudi Arabia [8]. Another more recent study performed at medical school in Bursa, Turkey has found that 30.5% of the participants have mild and moderate degree of depression while 8.5% have severe and extremely severe levels of depression [9].…”
Section: Introductionmentioning
confidence: 99%
“…However, too much stress affects learning and memory, with resultant morbidity 11,12 . Several studies have shown that intense pressures and demands of medical education can have detrimental effects on academic performance, physical health and psychological well-being of the students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from developing countries have reported stress among medical students but have underscored the role of academics as a source of stress 6,12,27,28 . Also these studies have either not assessed the coping strategies or did not use COPE inventory.…”
Section: Introductionmentioning
confidence: 99%